Hubungan antara tingkat pengetahuan perawat dengan perilaku perawat dalam pengelolaan sampah medis di ruang rawat inap RSUD Sukoharjo - Nurharyanti, Lilis; , Winarsih Nur Ambarwati, S.Kep, Ns, ETN, M.Kep; , Endang Zulaicha Susilaningsih, S.Kp., M.Kep (2016)
The hospital is one of health service units that produces medical waste. Medical waste management well be giving effect to health workers, patients and the patient's family. To be able to do medical waste management is needed good knowledge and behavior of nurses. The results of pre study at Sukoharjo hospital, there are activity of nurses of medical waste management like a needle, spuit, a bandage thrown away without separated. Research purposes this study is to know relationship between knowledge with behavior nurse of medical waste management in care ward of Sukoharjo hospital. The kind of study is research quantitative. Method use descriptive correlative, with h cross sectional approach. The population study are all of nurses as staff at care ward of Sukoharjo hospital, count 149 persons. The sample were 59 respondents. taken a sample of 59 respondents with a simple random sampling technique. Instrumentt study used knowledge questionnaire and uestionnaire tendency behavior questionnaire after validity and reliability tested. Data then tested with rank spearman test. The results showed that 26 respondents (44.1 %) with high knowledge, 30 respondents (50.8 %) with fair knowledge and 3 respondents (5.1%) with poor knowledge of medical waste management. There were 37 respondents (62,7%) with good behavior and 22 respondents (37.3%) good enough in medical waste management. The results of rank the spearman test obtained = 0.445 ; p value = 0,001. Conclusion: there were relationship between knowledge with behavior nurse of medical waste management in care ward of Sukoharjo hospital. More higher nurses knowledge, better behavior in medical waste management.